Diagnóstico y propuesta de un manual de valoración y clasificación de puestos para la compañía de carga pesada los Panchos S.A., de la ciudad de Yantzaza para el año 2016. - Abarca Villavicencio, Oscar Rodrigo (2018)
The present work called "DIAGNOSIS AND PROPOSAL OF A MANUAL OF VALUATION AND CLASSIFICATION OF POSTS FOR THE COMPANY OF HEAVY LOADING LOS PANCHOS SA, OF THE CITY OF YANTZAZA FOR THE YEAR 2016", has as main objective to realize a manual of valuation of positions for The heavy load company Los Panchos SA, to fulfill this purpose, required the use of the deductive method for the collection of information and inductive for the analysis of the data obtained, through research techniques such as the interview with the manager and surveys to the 10 workers who work in the company, the same one that allowed gathering fundamental information on how human talent has been performing. In the first instance, the theoretical framework that contains the information that supports the topic of research is presented, with arguments from other authors who endorse the information cited in this research work. In the same way it presents the necessary materials to elaborate the work and the use of the scientific, deductive, inductive, synthetic and descriptive methods and the techniques for the collection of information such as direct observation, interview to the manager and surveys at 10 officials of the Panchos heavy cargo company. The results show a historical overview of the company, the structural and functional organizational chart, which includes the positions it has, as well as a diagnosis of the results of the interview and surveys, then a function manual is developed where important information is presented. and valuable of each of the positions that make up the company which will avoid a duplication of functions, in addition to the valuation of the position, where the system was applied by points, with their respective stages from the definition of factors to the valuation of the jobs, where the following results were obtained, the total points according to the valuation is 1,860, the salaries received by the staff amount to 3,515, with this value the straight line equation was applied, which resulted in a slope of 1.87, taking the aforementioned value, the salary adjustment was made, with a valuation factor of 1.89, in order to determine the new wages. It is important to note that the new salary revaluation was made to the positions that are below the line of the salary adjustment that in total are 3 the same as the accountant, legal adviser and the driver. Finally, the conclusions and recommendations are presented, with the objective of systematically assessing the performance of the personnel in their position, which will determine if they meet the requirements that are required for the different positions of the company.